Enhanced visible-light-driven dye degradation via electron coupling between linear polymer nanoclusters and TiO2 nanoparticles - Khushabu Shekhawat; Hariom Gurjar; Dinesh Bhalothia; Anbalagan M. Ballamurugan; Ashima Bagaria (Discover Applied Sciences)
Abstract Considering the pressing demand for advanced environmental remediation technologies, particularly for the degradation of persistent organic pollutants, we report the development of organic–inorganic hybrid nanocomposites based on titanium dioxide (TiO2) coupled with linear polymeric chains polyethylene glycol (PEG) and polyvinylpyrrolidone (PVP) for enhanced visible light-driven photocatalytic dye degradation. These heterojunction materials (denoted as PEG@TiO2 and PVP@TiO2) were synthesized via a sol-gel route and systematically characterized using FESEM-EDX, XRD, FTIR, UV-Vis spectroscopy, and photoluminescence (PL) analysis. A strong interfacial interaction between TiO2 and the respective polymers facilitates efficient electron transfer, suppresses charge carrier recombination, and enhances photon absorption under visible light irradiation. This synergistic coupling significantly improves the photocatalytic breakdown of rose bengal dye, with PEG@TiO2 showing superior degradation performance compared to PVP@TiO2 and pristine TiO2. Our findings highlight the potential of polymer–TiO2 hybrid architectures as a cost-effective and sustainable pathway for environmental cleanup via solar-driven photocatalysis.